A Patient’s Journey with Immunoglobulin Light Chain (Al) Amyloidosis - Wint Wint Thu Nyunt; S Fadilah S Abdul Wahid, (Malaysian Journal of Science (MJS), 2025)
A 64-year-old man presented with progressively worsening difficulty in breathing and was subsequently diagnosed with immunoglobulin light chain (AL) amyloidosis. However, he was keen to seek a second opinion, causing a delay in initiating definitive treatment. His clinical manifestations included heart failure, chronic diarrhoea, symmetric lower extremity peripheral neuropathy, and autonomic neuropathy (postural hypotension). As he was non-transplant eligible and had financial constraints, he was initially treated with conventional chemotherapy [two cycles of cyclophosphamide + thalidomide + dexamethasone, followed by seven cycles of melphalan + prednisolone (MP)]. Throughout his disease course, he experienced chronic diarrhoea and profound oedema of lower limbs. He had to relocate to his son’s residence in Kuala Lumpur to enable frequent and regular hospital visits. He had impaired health-related quality of life (HRQoL); however, he had excellent family support. After nine cycles of conventional chemotherapy, the optimal response was not achieved. Bortezomib was added to MP therapy [bortezomib + melphalan + prednisolone (VMP) regimen]. Following three cycles of VMP, he achieved complete haematologic response (CR), resulting in symptomatic improvement and his eventual return to his hometown. He continued the same treatment regimen to control the disease. His hospital admissions decreased, and his HRQoL improved, although no organ response was noted. Three years later, he developed decompensated cardiac failure and passed away. His overall survival was five years and two months. This case report highlights that achieving CR leads to prolonged overall survival and improved long-term clinical outcomes, including HRQoL.